Awareness and acceptability of HIV pre-exposure prophylaxis (PrEP) among students at two historically Black universities (HBCU): a cross-sectional survey - Nwora Lance Okeke; Tony McLaurin; Ruth Gilliam-Phillips; David H. Wagner; Valerie J. Barnwell; Yolanda M. Johnson; Osaffo James; Padonda B. Webb; Sharon D. Parker; Bendu Hill; Mehri S. McKellar; John T. Mitchell (BMC, 2021)
Abstract Background Despite young African American adults (ages 18-24) being among the highest risk groups for HIV infection, little is known about their awareness of HIV pre-exposure prophylaxis (PrEP) - a once daily pill shown to be > 90% effective in preventing HIV. To explore awareness and acceptability of PrEP among college students in this demographic, we conducted a survey of attendees at two large historically Black universities (HBCU) in North Carolina. Methods We administered a 14-item questionnaire to students at two HBCUs in North Carolina between February and April 2018. Questions were formatted in a yes/no or multiple choice format. Questionnaire items specifically addressed PrEP awareness and acceptability. Surveys were administered to students at a campus health fair and while transiting the campus student union via iPad. Response to all questions was optional. We fit a logistic regression model to determine association of key demographic determinants with PrEP acceptability and awareness. Statistical analyses were conducted using SAS 9.4 (SAS, Cary, NC). Results Overall, 210 students participated in the survey, of which 60 completed all survey items as presented. The survey cohort was 75% female, 89% heterosexual and 39% freshmen. The mean age of respondents was 19.8 years (SD: 1.8). Fifty-two percent of survey respondents reported that they were aware of PrEP prior to the time of survey administration. Only 3% of respondents reported that they were on PrEP. The most common sources of information on PrEP were campus health services (24%) and non-social media advertising (15%). Of respondents who were aware of PrEP, 61% reported that they had heard about in the 6 months prior to survey administration, while only 19% say they were aware of it for more than a year. Regarding acceptability of PrEP, 58% of respondents reported that they would take a once a day pill for HIV if they were at risk. Our logistic regression analysis found no statistically significant associations between key demographic factors and PrEP awareness. However, persons who perceived themselves to be at risk for HIV acquisition were more likely to find once daily oral PrEP (relative risk 2.66 (95% CI 1.31-5.42)) as an acceptable prevention strategy than the rest of the survey cohort. Conclusions African American HBCU students are becoming aware of PrEP, and generally perceive the intervention as acceptable and worth consideration.